Evaluation the Association between Labor Dystocia and Birth Spacing in Iranian Women. - Meisam Akhlaghdoust; Nesa Zarbati; Zhila Amirkhani; Sara Naimi; Mohamadreza Sadeghi; Sahar Mohammadi Fateh; Mina Jafarabadi (Tehran University of Medical Sciences, 2014)
Objective:In view of the effect of hard labor on pregnancy outcomes and to determine risk factors, in this study, the effect of spacing between pregnancies was evaluated for probable effect on the incidence of dystocia in labor. Materials and methods:This is a cross - sectional study used the records of 210 pregnant women referred to Azad University hospitals between January 2000 and December 2012. Dystocia was diagnosed according to ICD-9-CM. Data were analyzed using statistical software Spss17. Results:It was found that in pregnancies with 2-4 years spacing between births normal delivery was more prevalent while in the group with 8-10 years spacing labor dystocia was more prevalent. Conclusion:Based on the findings of this study the interval between pregnancies has a significant effect on labor dystocia. Increasing the spacing between pregnancies more than 8 years is a risk factor for dystocia.